Visitors Preferences and Spatial Interaction Analysis of Taman Krida Wisata and Pijar Park - Fauzi Janu Amarrohman; Hana Sugiastu Firdaus; Wildan Ruliyono (Politeknik Negeri Batam, 2023)
Taman Krida Wisata and Pijar Park are located on Kudus Regency. Culture and Tourism Departement of Kudus Regency informed that Taman Krida Wisata is a family recreation park with various animal statues.Youth, Sports, and Tourism Departement of Central Java informed that Pijar Park is a tourist destination that offers a tourism concept with a variety of interesting attractions and facilites. Taman Krida Wisata has an artificial tourist attraction, while Pijar Park has natural and artificial attractions. In 2020, Taman Krida Wisata had 2.588 visitors, while Pijar Park was 723. In addition, in 2019, Taman Krida Wisata was visited by 22.836 tourists, while Pijar Park was visited as many as 3.623. The two tourist areas affect the surrounding economy because there are people who take benefit from the existence of the tourist area. Besides, Taman Krida Wisata and Pijar Park have different management, visitor’s distribution, and tourist destination facility. Therefore, Hedonic Pricing Method is used to determine the value of visitors prefrences in the area and the Gravity model to determine the flow of movement berweetn the two tourist areas with nearest district, office zone, and central economic zone. There are 9 variables are used for HPM, namely tourism facility, transportation, lodging, gift center, entrance fee, health facilities, worship facilities, shopping complex, and public service area. HPM Taman Krida Wisata used 131 sample, while Pijar Park used 135 sample. Taman Krida Wisata has a hedonic value with intervals 4.000-4.189, while Pijar Park has a value 3.976-4.160. Based on the calculation of spatial interaction, Taman Krida Wisata has a higher value than Pijar Park.